Updated discussions on 'Hybrid multiple criteria decision-making methods: a review of applications for sustainability issues'. Issue 1 (26th July 2018) - Shen, Kao-Yi; Zavadskas, Edmundas Kazimieras; Tzeng, Gwo-Hshiung
Abstract: A recent review discussed a variety of hybrid multiple criteria decision-making (HMCDM) methods on the subject of sustainability issues. Some soft computing techniques, such as the fuzzy set, have contributed significantly to HMCDM studies, emulating the imprecise or uncertain judgments of experts/decision makers in a complex environment. Nevertheless, a new rising trend in HMCDM, known as multiple rule-based decision-making (MRDM), which has the advantage of revealing understandable knowledge for supporting systematic improvements based on influential network relation maps (INRM), was not discussed in the review. This study therefore attempts to extend the review by introducing recent developments and the associated work on MRDM for solving practical problems, updating the discussion.